Acral manifestations of fungal infections - Kutlubay, Zekayi; Yardımcı, Gürkan; Kantarcıoğlu, A. Serda; Serdaroğlu, Server (Elsevier Science Inc., 2017)
Fungal infections, which are named according to the body site involved, can affect any skin area, the fingemails, or the toenails. Numerous fungal agents are responsible for both superficial and deep fungal diseases. Dermatophytes and Candida spp are the most common causative organisms on the surface of the hands, feet, and nails of patients with superficial fungal diseases; however, although deep fungal infections of the skin are less common compared with superficial fungal diseases, their incidence is increasing worldwide due to cross-border travel. Most superficial fungal diseases are diagnosed clinically, but sometimes direct microscopic examination with potassium hydroxide and fungal culture may be necessary for diagnosis, especially in patients suspected of having tinea incognito. In cases of superficial fungal infections except for onychomycosis and tinea incognito, topical treatments are usually sufficient and effective, but systemic treatments may be required in recalcitrant cases. Deep fungal diseases may resemble each other clinically; therefore, the organism must be identified with laboratory methods and should be treated for a long period. We review the most important clinical, diagnostic, and therapeutic aspects of fungal diseases. This paper covers fungal problems encountered both in hospitals and in general practice.
WOS: 000390087700005
PubMed ID: 27938809
Keywords: Acral Manifestations; Fungal Infections; Dermatology